Analysis of the Needs Augmented Reality-Based Learning Media: Spatial Structure Material in Junior High Schools - Mucti, Alfian; Nurmala R; Hermansyah, Hermansyah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Acquiring knowledge in geometry, especially three-dimensional geometry, necessitates robust visualization and spatial reasoning abilities. In practice, students frequently encounter challenges in perceiving three-dimensional shapes when solely provided through two-dimensional representations in textbooks or on classroom boards. This study aims to examine the preliminary requirements for creating Augmented Reality (AR)-based educational resources for three-dimensional geometry at the junior high school level, as a component of the Analysis phase of the ADDIE development model. The research employed a descriptive qualitative approach, with data collected through semi-structured interviews involving one mathematics teacher and two eighth-grade students at Junior High School 7 Tarakan. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results demonstrate that students have challenges in visualizing three-dimensional structures, especially in tasks involving composite solids and spatial perspectives. Traditional learning media are deemed inadequate in delivering sufficient visual experiences and are restricted in their application. Simultaneously, both educators and learners articulated a want for interactive, flexible, and smartphone-accessible technology-based learning resources. Augmented reality media are considered to have the capacity to enhance students' comprehension of three-dimensional geometric topics by providing tangible learning experiences through manipulable three-dimensional visuals. These findings lay a crucial foundation for the future design and development of AR-based educational media.